Copper(I) Halide Complexes with Triphenylphosphine and N,N’- Diphenylthiourea - Ladawan Duangmuengmai (Prince of Songkla University, 2011)
Thesis (M.Sc., Chemical Studies)--Prince of Songkla University, 2010